SOG'LIQNI SAQLASH MUASSASALARIDA STRATEGIK MENEJMENT: AHOLI SALOMATLIGI KO'RSATKICHLARI VA DEMOGRAFIK JARAYONLARNING TIBBIY-IJTIMOIY TAHLILI - Alimbayeva Sevara Azamatovna; Sohibov Oybek Mardonovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2026)
Transformations in global healthcare demand innovative management in healthcare institutions (HCIs). The study evaluated health management systems, morbidity dynamics, demographic aging, and disability determinants. Based on retrospective records of N=1450 patients and 2018-2023 demographic reports, the correlation between non-communicable disease growth and socio-economic factors was analyzed (p < 0.05). Results confirmed that in digitalized and screening-oriented institutions, early diagnostic rates are 34.2% higher compared to traditional ones. This approach holds strategic significance for HCI improvement. The "Medical and Demographic Risk Assessment" model is recommended as a practical solution.